Bahrain's Surviving Dynasty Struggles and Successions. 1783-1932. - Matar, Mohamed (Exeter Critical Gulf Studies., 2023)
The Al Khalifa of Bahrain is a long-standing dynasty that has established dispute resolution measures to overcome intra-tribal ambitions for power and wealth, replacing extra-constitutional rulership succession with primogeniture. Since their control over Bahrain began in 1783 until the British withdrawal from the Gulf in 1971, the Al Khalifa introduced ten senior ruling shaykhs, seven of whom experienced turbulent successions, and faced in-house rivalries and.